Under the sword of Damocles: Exploring the well-being of university academics during a crisis - Subban, Pearl; Laletas, Stella; Creely, Edwin; Southcott, Jane; Fernandes, Venesser (Frontiers in Education, 2022)
Prompted by the wide-spread impact of the global pandemic on the higher education sector in Australia, this study explores the wellbeing and mental health of university academics who were caught in this altering landscape. This mixed-methods study has three objectives. Firstly, the study involved the design and development of an instrument to measure the wellbeing of university teachers. Secondly, the new instrument was administered to a randomly drawn sample of university academics, in order to validate its use. Thirdly, the study sought to identify possible strategies utilized by participants during times of high pressure, conflict and stress. As an initial validation study, the project involved scale design, generating a tool which measures the wellbeing of university academics, especially during times of crisis. The measurement tool was constructed in four parts drawing on the established formula of academic workload: Teaching, Research, Service/Engagement, with Part 4 seeking out demographic variables for analysis. Findings suggested that most academics were concerned about the maintenance of their research output and teaching workloads. Maintaining responsibilities as care-givers and parents of school-going children proved challenging. Many conceded that maintaining equilibrium was complex. It is anticipated that the scale will be an effective means of quantifying academic wellbeing especially during a crisis, thereby offering a valid instrument to university leaders, when considering staff security and comfort, in the contemporary context.